EFFORTS TO BUILD SCHOOL BRAND IMAGE TO ATTRACT NEW STUDENTS - Doni Kurniawan; Yetri Yetri; Farida Farida; Riyuzen Praja Tuala; Ahmad Fauzan (Universitas Islam Negeri (UIN) Sumatera Utara, 2026)
This study aims to analyze the efforts of SMA Negeri 2 Bandar Lampung in building its brand image as a means of increasing the interest of new students. The approach used is descriptive qualitative phenomenological with interview, observation, and documentation techniques. The results of the study show that brand image formation is carried out through three main dimensions, namely corporate image, user image, and product image. Corporate image is built through academic and non-academic achievements, teacher professionalism, and public communication that is adaptive to digital developments. User image is formed through the development of religious, disciplined, and inclusive character, which reflects the ethical and integrity-based behavior of students. Meanwhile, product image is demonstrated through modern facilities, quality educational services, and excellent programs that are relevant to the needs of students. The synergy of these three aspects strengthens public trust, increases the number of applicants each year, and affirms SMANDA's position as a competitive and character-building educational institution in Lampung Province.